Increasing energy values of biscuits with tempe purée and sardines flour as the ingredient substitutions - Slamet Widodo; Andi Hudiah (Universitas Negeri Makassar, 2022)
Abstract. This research and development study aims to investigate the energy values of biscuits made of tempe purée ad sardines flour (sardinella). The experiment was conducted in the Laboratory of Home Economics Department (PKK) in Engineering Faculty of Universitas Negeri Makassar. The used data collection technique is documentation from proximate analysis. The used data analysis technique is descriptive analysis. The process of making biscuits using tempe purée and sardines flour starts with weighing all the ingredients, mixing, weighing the dough for 1 biscuit, moulding the dough, placing in the oven and baking, remove from the oven and cooling, then packing the biscuits. The results showed that the nutritional values based on the proximate test of the biscuit formula with the substitution of tempe purée and sardines flour showed that the calorie value increased to 7.8 kcal, fat value increased to 1.72 grams, and calcium value increased to 5.59 grams. Keywords: Biscuit, Sardines Flour, Tempe Purée